Influencia de las características de flujo en la cavitación de una turbina Darrieus (2017)
This paper presents and discussed a two dimensional Computational Fluid Dynamics (CFD) implementation of a Darrieus cross flow marine turbine. Maãitre's work was utilized to: create a mesh family, set the simulations parameters and compare the results. This entire work was accomplished using only Open Source Software. The mesh was created in GMSH, flow was solved in OpenFoam and the results were visualized and analyzed in Paraview. PimpleFoam and InterPhaseChangeFoam were employed while assuming incompressible, isothermal, transient, turbulent and Newtonian flow. k-omega SST was selected as turbulence model and Kunz for the transfer model. Results were taken in a range of tip speed ratio (?) and compared with Maãitre's reported results, achieving substantial similarities. Significant variances were found between instantaneous power coefficient (cp ) for the reference simulation and with the cavitation model. Numerical results show the influence of the free flow velocity and pressure in the cavitation and the performance of the turbine.--Tomado del Formato de Documento de Grado.